Trends of Hepatitis Virus Infections in a Tertiary Care Hospital in Nepal, 2012-2023 (Tribhuvan University Journal of Microbiology, 2024)
Objectives: To monitor the trends of incidence of different hepatitis virus infections during 2012–2023 in a tertiary care hospital in Nepal.Methods: A descriptive study was conducted using demographic and serological data from 2012 to 2023 at Tribhuvan University Teaching Hospital. The serological tests were performed by enzyme-linked immunosorbent assays from the patient’s serum.Results: The incidence of HAV infections showed a downward trend from 2012–2016 (37.6%- 17.7%), increased in 2017–2019 (33.9%-27.8%), and then gradually decreased to 10.2% in 2023. In case of HEV infection, the incidence did not show any trend over the ten years period (from 2012-2018: 5.4%-13.3%; 2020: 7.1%; 2021:14.7%; 2023: 4.2%). The incidence of HBV infection was nearly unchanged between 2.5-3.1% from 2012-2023, the incidence of HCV infection was between 0.7-1.8% during the same period. The proportion of male cases was higher for all hepatitis infections and adult cases (15-47 years old) were in higher proportions except hepatitis A.Conclusion: While the incidence trends of hepatitis B infections have been nearly the same over the past ten years, the trends of hepatitis A, E, and C infections are declining. Extensive preventive efforts are essential for reducing the infection rates to a low level.